Essential Skill and Knowledge Required for Health Data Professionals: A Content Analysis of Job Advertisements. - Flite, Cathy A.; Foster, Susan; Houser, Shannon H.; Hunt, Thomas J; Kinnerson, Lakesha; Morey, Angela; Peterson, Jennifer; Pope, Roberta Darnez (Perspectives in Health Information Management)
Healthcare organizations rely on skilled health data professionals to enhance organizational effectiveness and patient care. This study analyzes recent job postings to identify the prevalent skills, competencies, and technical skills that healthcare organizations are looking for when hiring health data professionals. A content analysis of 34 unique job postings provides key insights into the skill sets and knowledge necessary to fulfill these roles. The findings revealed a diverse range of skills, including analytics, SQL proficiency, business acumen, data visualization, and essential soft skills such as problem solving, interpersonal communication, and project management. Additionally, the education requirements indicate a need for bachelor's degrees or higher for these positions. These findings serve as a valuable resource for both educators and employers in guiding curriculum development and refining hiring practices.